PENINGKATAN KETERAMPILAN SMASH KEDENG PADA PERMAINAN SEPAK TAKRAW PADAANAK SEKOLAH DASAR - Aji, Tri (Universitas Negeri Semarang, 2010)
This research was conducted at State Elementary School 04 of KarangtalunCilacap involving 16 male six graders. The observation of three cyles showed that thestudents improved their smash skill. The basic movement skill in cycle I improvedfrom 25% to 42%. In cyle II, the basic movement skill improved from 42% to 57%. Incycle III the improvement was from 57% to 78%. The results indicated that the theindicator was achived in that 75% players mastered the expected smash basicmovement. Therefore, it is concluded that skill improvement could improve thekedeng smash skill inTakraw game for elementary students in Cilacap Regency.Kata kunci : smash kedeng, permainan sepak takraw, anak sekolah dasar